(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
Credit plays a significant role in the development of economic science. It promotes the development of international economic relations and accelerates the process of capitalization of profits and concentration of production. Credit stimulates the development of production forces and accelerates the formation of sources of capital to expand reproduction based on the achievements of scientific and technological progress. It has a significant impact on the development of economic relations between industries, as well as regions and countries. The article examines the role of credit and its functions in the development of a market economy.